A qualitative analysis of follow-up interviews with SLE patients from the “living well with lupus” study - Smaira, Fabiana Infante; Mazzolani, Bruna Caruso; Sieczkowska, Sofia Mendes; Romero, Marina; Pasoto, Sandra; de Sá Pinto, Ana Lúcia; Lima, Fernanda Rodrigues; Benatti, Fabiana Braga; Roschel, Hamilton; Weber, Mary Beth; Gualano, Bruno (Frontiers in Medicine, 2025)
Objectives“Living Well with Lupus” (LWWL) consisted of a lifestyle intervention program tailored for patients with systemic lupus erythematosus (SLE) and high cardiovascular risk. In the present study, we assessed the maintenance of behavior changes related to physical activity and healthy eating after the 6-month LWWL program.MethodsSemi-structured interviews were conducted with 25 participants from the intervention group between 7 and 28 months after the program ended. Using qualitative content analysis, themes regarding behavior maintenance and perceived effects were identified.ResultsOur findings suggest that maintaining the new lifestyle behaviors resulted in health benefits such as weight loss, pain reduction, and improved well-being; whereas worsening health, with increased anxiety, fatigue, and pain were reported among those that did not maintain the new behaviors over time. Most importantly, the main barriers to maintaining lifestyle changes included adverse weather conditions, family conflicts, health problems, and high work demands. On the other hand, family and professional support were highlighted as facilitators.ConclusionThese results suggest the importance of ongoing support to promote adherence to lifestyle changes in SLE patients. Integrated interventions with family and professional support are essential for sustaining these changes, highlighting the need for a holistic approach to health promotion for patients with chronic conditions.